A large pholidosaurid in the Phu Kradung Formation of north‐eastern Thailand. (18th November 2013) - Martin, Jeremy E.; Lauprasert, Komsorn; Buffetaut, Eric; Liard, Romain; Suteethorn, Varavudh; Angielczyk, Kenneth
Abstract In the early 1980s, the remains of a large crocodilian, consisting of a nearly complete lower jaw, were referred to a distinct species of Sunosuchus, S. thailandicus. The specimen was recovered from a road‐cut near Nong Bua Lamphu, north‐eastern Thailand, in the upper part of the continental Phu Kradung Formation, and then considered Early to Middle Jurassic in age. Since then, this age has been revised and most of the formation is now considered Early Cretaceous, although a Late Jurassic age is possible for its lowermost part. Here, we report for the first time cranial elements associated with mandibular remains assignable to 'S'. thailandicus. An attribution to Pholidosauridae is proposed on the basis of premaxillary morphology, and the original referral of this taxon to the goniopholidid Sunosuchus is discarded. A new genus name Chalawan now designates the originally described material of S. thailandicus. Nevertheless, the newly described specimen shares a characteristic with both 'traditional' Goniopholididae and Pholidosauridae: the presence of a depression located on the lateral wall of the maxilla and jugal. A phylogenetic analysis confirms the inclusion of both Goniopholididae and Pholidosauridae into a common clade, Coelognathosuchia tax. nov. Although the new Thai skull is much fragmented, its original shape is reconstructed and is compared with other pholidosaurid genera, namely Elosuchus, Meridiosaurus, Oceanosuchus, Pholidosaurus, Sarcosuchus and Terminonaris. The presence of the genus Sunosuchus being highly questionable in Thailand, it cannot be used as evidence to link the Chinese and Indochinese blocks. Instead, the recognition of a freshwater pholidosaurid in a continental formation of the Indochinese block suggests that early in their evolutionary history, these crocodilians, already known from Europe, Africa and South America, were more widely distributed along the northern margin of the Tethys than previously recognized.